KONSEP ONE REGULATION AND ONE BODY DALAM PENGATURAN JUAL RUGI DI INDONESIA - Lusy Febriana Kurnia (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract This article reviews concept of loss-sale arrangements in the perspectives of anti-dumping and business competition laws in Indonesia. Review is considered helpful to harmonize loss-sale arrangements in Indonesia because two laws and two agencies are overlapping to each other in this case that may result in the ambiguousness of loss-sale arrangement laws in Indonesia. Research type is normative juridical with several approaches such as statute approach, comparative approach and conceptual approach. Result of research indicates identification disharmony of loss-sale arrangements and loss-sale arrangements in the perspectives of anti-dumping and business competition laws in Indonesia use concept one regulation and one body. Key words: harmonization, dumping, predatory pricing Abstrak Artikel ini mengkaji tentang konsep pengaturan jual rugi dalam perspektif hukum antidumping dan hukum persaingan usaha di Indonesia, yang bertujuan untuk mengharmoniskan pengaturan jual rugi di Indonesia karena terdapat dua peraturan dan dua lembaga yang saling tumpang tindih yang berakibat pada ketidakpastian hukum pengaturan jual rugi di Indonesia. Penelitian ini merupakan penelitian yuridis normatif dengan menggunakan pendekatan perundang-undangan, pendekatan komparatif, dan pendekatan konsep. Hasil penelitian merujuk pada identifikasi disharmoni pengaturan jual rugi dan pengaturan jual rugi dalam perspektif hukum antidumping dan hukum persaingan usaha di Indonesia melalui konsep one regulation and one body. Kata kunci: harmonisasi, dumping, predatory pricing